An Analysis of Action Research Studies Conducted by Teachers in Sri Lankan Schools - G.D. Lekamge; J. Thilakeratne (The Open University of Sri Lanka, 2019)
Action research is becoming popular in the school system as a viable mean for empowering teachers. It provides teachers the opportunity to improve their reflective practice and to implement solutions to problems they face in the teaching-learning process. Considering the potential benefits of action research to teachers, students and school community at large, the Ministry of Education of Sri Lanka had launched a project aimed at empowering teachers with required skills and motivating them to conduct action research studies. About 84 teachers who had sent their research proposals in response to an open invitation sent by the Ministry of Education in early 2017 were called for a series of workshops through which their original proposals were fine-tuned and knowledge and skills on action research were enhanced. This paper analyses the nature of problems considered by teachers for their action research studies, the innovative strategies adopted for the intervention process and the observations and reflections made during the intervention process on the changes experienced by participants. As the analysis reveals, teachers are capable in applying innovative strategies as solutions to the problems in their teaching learning process. Further, it is evident that many students who had problems in coping with day-to-day activities in their classrooms benefitted through the interventions. It is recommended that school authorities should develop a supportive environment within their schools to motivate teachers towards action research studies as they provide on-the-spot solutions to the problems in the teaching-learning process.